Kryminalizacja niealimentacji jako wyraz karnoprawnej ochrony rodziny i opieki - Płońska, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The article deals with the issues related to the breach of the maintenance obligation, which in Polish criminal law system is referred to as a non-alimony offence. The author points out the changes that have been introduced to Article 209 of the Penal Code on the basis of the amendment dated on March 23rd, 2017. The aim of the legislator was to strengthen the fulfillment of the duty of care by satisfying the material needs of people who are not able to satisfy them on their own. The amendment to the Article 209 of the Penal Code was in principle introduced to constitute a criminal law instrument aimed at satisfying the needs of citizens more fully by ensuring that the protection rights of the entitled persons are provided. The aim of this study is to indicate the problems faced by contemporary criminal law in accordance to the issue of non-alimony and to attempt to evaluate them in terms of goals assumed.
Keywords: non-alimony; maintenance obligation; criminal law; article 209 CC; family